Review Article on the Use of Lime Mortar in Heritage Buildings - Duaa M. Abed; Jasim M. abed; Zaid H. Al-Saffar (NTU Journal of Engineering and Technology)
This review article aims to comprehensively explore the historical significance and modern applications of gypsum, lime mortar, and pozzolanic mortar in heritage buildings. The study will investigate their properties, benefits, and limitations in the context of preservation and restoration, considering the impact of traditional construction practices on the structural integrity and cultural value of heritage structures. By analyzing existing literature, this review aims to formulate a research plan to further enhance our understanding and utilization of these materials in conserving invaluable heritage buildings